High pressure XANES and XMCD in the tender X-ray energy range. Issue 3 (2nd July 2016) - Wilhelm, F.; Garbarino, G.; Jacobs, J.; Vitoux, H.; Steinmann, R.; Guillou, F.; Snigirev, A.; Snigireva, I.; Voisin, P.; Braithwaite, D.; Aoki, D.; Brison, J.-P.; et al.
ABSTRACT: We have developed an experimental setup at the ESRF beamline ID12 dedicated to X-ray absorption and magnetic circular dichroism measurements at high pressure adapted for the tender X-ray energy range and compatible with low temperatures and with high magnetic field. The focused incoming X-ray beam passes through a thin diamond disk attached to a fully perforated diamond anvil and X-ray fluorescence photons from the sample are collected in back-scattering geometry through the same diamond disk. The pressure in the cell is measured using the ruby luminescence through a full diamond anvil. The highest pressure attainable with this diamond anvil cell (DAC) depends on the thickness of the diamond disk and it is above 16 GPa for a 80-μm thick plate and exceeds 4.5 GPa in the case of 30-μm diamond disk. Excellent performances of this setup in the tender X-ray range are illustrated with X-ray absorption near-edge structure studies of the phase transitions in KCl at the potassium and chlorine K-edges (3.61 and 2.82 keV, respectively) as well as in CdS at the sulfur K-edge (2.47 keV). This DAC together with a dedicated total fluorescence yield (TFY) detector could be mounted in the main heat exchanger of a cryostat and inserted in a bore of a superconducting magnet, this makes possible to perform X-ray magnetic circular dichroism (XMCD) experiments at low temperature, high magnetic field and high pressure. Feasibility of this approach is shown with the XMCD results obtained at the U M 4, 5 -edges in ferromagnetic superconductor UGe 2 .